GENERALIZED MODEL OF DOPPLER SIGNAL OF THE HYDROACOUSTIC LOG - Onyshchuk, Oleh; Baras, Svjatoslav (Scientific Works of Vinnytsia National Technical University, 2015)
The mathematical model has been analyzed and the computer physical modeling of Doppler signals has been performed. As a result, the model of the Doppler signal of the hydroacoustic log has been proved and generalized.